Epoetin Alfa: A Cause of Coronary Artery Thrombosis - Muhammad Umer Siddiqui; Yelena Galumyan; James Klein; Zunaira Naeem; Aron Schwarcz (Case Reports in Cardiology)
Introduction. Epoetin alfa is an erythrocyte-stimulating factor. We here present a case of an anemic patient, who was given epogen before a coronary artery bypass (CABG) surgery and developed periprocedural myocardial infarction. To our knowledge, there has been no previous case reported of epogen causing myocardial infarction. Case Presentation. 66-year-old female presented with substernal chest pain. EKG showed ST segment elevations in aVf and L-III. Patient underwent left heart catheterization (LHC) and had triple vessel disease. A bare metal stent was placed in RCA. Patient continued to have symptoms after discharge and presented to the ED again with these complaints. She underwent coronary artery bypass surgery (CABG). Before the procedure, patient’s hemoglobin was 11.1 grams/deciliter and was given epogen to raise hemoglobin level. Postoperative day (POD) #1 patient had ST elevations in inferior and anterolateral leads. She was diagnosed with periprocedural myocardial infarction. Patient underwent repeat LHC, which identified obstruction of saphenous vein graft (SVG). Hypercoagulable workup was negative for any disease and the patient was diagnosed with epogen induced early graft occlusion. Conclusion. Epogen administration can cause myocardial infarction and coronary artery thrombosis. We suggest that physicians use epogen very cautiously, especially in population who has underlying coronary artery disease.